2014
DOI: 10.1007/s13149-014-0386-1
|View full text |Cite
|
Sign up to set email alerts
|

Séroprévalence de l’Ag HBs et de l’anticorps Anti VHC chez les personnes infectées par le VIH1 à N’Djamena, Tchad

Abstract: This is a prospective study conducted as part of a voluntary testing for HBV, HCV and HIV. The aim of the study is to determine the seroprevalence of HBs Ag and anti-HCV antibodies among HIV infected people and a control group of HIV negative people. HIV prevalence among newly diagnosed volunteers is 9.1%. The overall seroprevalence of HBs Ag and anti-HCV antibodies is respectively 13.5% and 2.0%. The seroprevalence of HBs Ag and anti-HCVantibodies in the control group (HIV-negative) is respectively 12.2% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
2
7
1
Order By: Relevance
“…Indeed, Chad is a country of generalized HIV epidemic with the adult prevalence rate at 3.5% in N’Djamena [60], as observed in our series. Chad is also a country of high HBV and HCV infections prevalences in adults, and in our study the prevalences of these viral infections were of the same order as those previously reported in N’Djamena in 2014 by Bessimbaye and colleagues [61]. Consequently, the rates of these three epidemiological infectious markers observed in our series tend to reflect the general epidemiology in Chad, thereby making our study sample close to the general population in Chad.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Indeed, Chad is a country of generalized HIV epidemic with the adult prevalence rate at 3.5% in N’Djamena [60], as observed in our series. Chad is also a country of high HBV and HCV infections prevalences in adults, and in our study the prevalences of these viral infections were of the same order as those previously reported in N’Djamena in 2014 by Bessimbaye and colleagues [61]. Consequently, the rates of these three epidemiological infectious markers observed in our series tend to reflect the general epidemiology in Chad, thereby making our study sample close to the general population in Chad.…”
Section: Discussionsupporting
confidence: 88%
“…Study women were referred to the clinic “ La Renaissance Plus” of N’Djamena, although they were not part of the patients from the clinic, avoiding the obvious bias of recruitment by health care facilities. Furthermore, 9 (3.5%), 19 (7.5%) and 8 (3.2%) study participants were HIV-, HBsAg- and HCV-specific antibody- positive, respectively, in accordance with the high endemicity of these three major chronic viral infections in Chad [60, 61]. Indeed, Chad is a country of generalized HIV epidemic with the adult prevalence rate at 3.5% in N’Djamena [60], as observed in our series.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, study participants referred to clinic “ La Renaissance Plu s”, N'Djamena, were not patients from the clinic, avoiding the obvious bias of recruitment by health care facilities. Furthermore, 9 (3.5%), 19 (7.5%), and 8 (3.2%) study participants were HIV-, HBsAg-, and HCV-specific antibody positive, respectively, in accordance with the high endemicity of these three major chronic viral infections in Chad [48, 49]. However, our study has limitations.…”
Section: Discussionmentioning
confidence: 71%
“…This same coinfection was reported with HBsAg-Syphilis by Nambei et al with 12.5% and that of HIV and HCV which were respectively 12.5%, but this prevalence remains higher than that obtained in our study. In 2014, Bessimbaye et al [18] in Chad reported a prevalence of HBsAg at 13.5% in people infected with HIV. This suggests that the prevalence of HBsAg is significantly elevated in blood donors and in the general population.…”
Section: Resultsmentioning
confidence: 99%